Implementation of General Pre-Anesthesia Assessment in The General Installation Room in The Surgical Installation Room of X Regional Hospital - Ghazaly, Yusdi; Utomo, Ndaru Ari (Westscience Press, 2025)
Anesthesia services are part of perioperative services that have a major influence in determining the success of adequate surgical procedures and avoiding the risk of anesthetic injury to patients. Anesthesia providers in carrying out their professional practices are authorized to provide anesthesia care services in pre-anesthetic assessments. To determine the implementation of pre-anesthetic assessments in patients with general anesthesia in the Central Surgery Installation Room of Buleleng District Hospital. This study used a qualitative research design, and a Multiple Case Study research method with a Descriptive approach. The number of participants in this study was 2 participants who met the inclusion criteria. Data collection tools used interview checklists, Observation sheets, and Pre-Anesthesia Assessment Implementation Documentation sheets. The results of this study on the examination of the participant's anamnesis carried out an assessment using the Foundational Four and Sacred Seven, on the physical examination the participant did not carry out BMI and peripheral nerve disorders. And in the pre-anesthesia documentation, the participant wrote the assessment results on the documentation sheet during the operation and post-operation. The anesthesia technician in carrying out the assessment of the patient's anamnesis, reviewing the physical examination, supporting examination and the patient's psychology almost in accordance with the applicable SOP, except for the examination of BMI, peripheral nerve disorders, providing therapeutic greetings at the end of the procedure and in documenting the procedure did not comply with the applicable SOP, this was due to the short time during pre-anesthesia.